Developing Speaking Material Based on Storytelling by Using YouTube in The Tenth Grade Students of SMA Negeri 1 Bahorok Academic Year 2023/2024 - Al Khairi, Ilham; Risnawaty, Risnawaty; Asnawi, Asnawi (International Journal of Educational Research Excellence (IJERE), 2025)
This study aimed to develop the leaning module in speaking based on storytelling by using YouTube in the tenth grade students of SMA Negeri 1 Bahorok academic year 2023/2024. The research was used to identify the effectiveness and the result the combination between the old techniques with the modern technology like YouTube. There were 12 students as the participants who study in SMA Negeri 1 Bahorok. The methodology used in this study was research and development by Borg and Gall that includes ten steps of the process. There were some questionnaires give to the students and expert to get the rich. In collecting the data, pre-test and post-test were used to get the distinction between the old and the new learning activity. The test measured by using N-Gain Score to obtain the effectiveness of the new design applied in the class. Moreover, the questionnaires were also given to the experts. Both of them gave the positive feedback to the use of YouTube in the speaking storytelling module. The result indicates that the students need to utilize the technology in their learning activities. By getting 59.18% in N-Gain score, it shows the effectiveness of the speaking based on storytelling technique by using YouTube. The expert also validated several aspects such: content, language, feasibility and design. Most of them were in moderate and high position measured by using Aiken’s validation. In short, the learning module can be applied in the educational program. In other case, it also can be implemented in other genres.